PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP SUSTAINABILITY REPORT DISCLOSURE (Studi Kasus Pada Perusahaan Sektor Pertambangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Sari, Dian Novita (Review of Accounting and Business, 2023)
This research aims to determine the Effect of Good Corporate Governance Mechanism and Financial Performance on Sustainability Disclosure (Case Study on Mining Sector Companies Listed on the Indonesia Stock Exchange in 2020-2022). In this study, the method used is a descriptive method with a descriptive approach with secondary data obtained from financial statements and sustainability reports. The selected population is Mining Sector Companies with a population of 62 companies. The sampling technique used is purposive sampling of 15 samples. The technique carried out in analyzing this data is panel data regression analysis. The results of this study show that the board of directors, audit committee, independent commissioners, profitability, liquidity and company size have a significant influence simultaneously on sustainability report disclosure. Partially, the board of directors, audit committee, profitability and company size have a significant effect on sustainability report disclosure, while independent commissioners, liquidity do not have a significant effect on sustainability report disclosure.